Psychological well–being and Marital Commitment of Mothers of ADHD Children based on Cognitive-emotional Regulation: The mediating role of Communication Skills - Keshavarz, Somayeh (Iranian Journal of Neurodevelopmental Disorders, 2024)
Purpose: The purpose of this research was to determine the mediating role of communication skills on the relationship between cognitive-emotional regulation with psychological well-being and marital commitment of mothers who have hyperactive/attention deficit children. Methods and Materials: A cross-sectional correlational study was designed to investigate the correlation between variables. The study population consisted of mothers of children with Attention-Deficit/Hyperactivity Disorder (ADHD) attending elementary schools in Karaj during the year 2024. The study participants were recruited through convenience sampling technique. The instruments included Ryff’s psychological well-being questionnaire (1989), Garnefski et al.’s cognitive regulation of emotion (2005), Adams and Jones’s marital commitment (1997), and Jerabek’s communication skills (2004). Descriptive statistics, such as means and standard deviations, were used to describe the data. For inferential analyses, Pearson correlation coefficients and structural equation modeling, and Sobel Statistic were used to examine the correlation between variables. Data analyses were conducted using SPSS and AMOS version 24. Findings: The results demonstrated that positive emotion regulation strategies, mediated by communication skills, significantly predicted both psychological well-being (β = 0.17, p = 0.001) and marital commitment (β = 0.22, p = 0.001) in mothers of children with ADHD. Conversely, negative emotion regulation strategies, mediated by communication skills, significantly predicted lower psychological well-being (β = -0.14, p = 0.001) and marital commitment (β = -0.19, p = 0.001). Conclusion: In addition, the findings indicated that communication skills mediated the relationship between positive and negative emotion regulation strategies, psychological well-being and marital commitment of mothers of children with attention deficit hyperactivity disorder.